Optimation of Avicel PH 102 with Cab-O-Sil M-5P Ratio and Crospovidone Concentration on Liquisolid System Piroxicam Tablet - T.N. Saifullah Sulaiman; Rani Puspita; Mutmainah Mutmainah (Majalah Farmaseutik, 2017)
Piroxicam is slightly soluble, so it should be developed in a liquisolid system of tablet dosage form to increase its solubility in gastrointestinal tract. Factorial design was applied to optimize the formula of liquisolid system piroxicam tablet by using four formulas: run  I (18%A-2%B), run II (45%A-2%B), run III (18%A-5%B), and run IV (45%A-5%B). Component A is the ratio of Avicel PH 102 with Cab-O-Sil M-5P whether B is the concentration of crospovidone. Optimum formula was determined by superimposed contour plot from various parameters: hardness, friability, disintegrating time, and dissolution concentration (C45) using Design Expert software. Based on superimposed contour plot, optimum formula area was obtained in the range of 18-45 of Avicel PH 102 with Cab-O-Sil M-5P ratio and 2-5% of crospovidone concentration.